Integrando fenologia da frutificação e consumo de frutos por vertebrados silvestres em uma área protegida de floresta tropical sazonalmente seca - Silva, Érica Emanuela de Medeiros e (2019)
The climate of the Caatinga is highly seasonal, but little is known about the influence of this seasonality on the interactions between plants and frugivorous animals in this region. This study aimed to describe and evaluate the phenology of the fruiting of zoocoric plants and the use of this resource by wild vertebrates in a protected area. Four specific objectives were proposed: (i) to describe the seasonal variation of the fruiting of zoocoric species in a dry forest area, (ii) to evaluate the influence of rainfall on the seasonal variation of the fruiting of these species, (iii) to identify the periods of absence of zoocoric fruit production for the wild fauna during the one year period, and (iv) to evaluate the relative importance of each fruit species in the diet of the animals. The study area comprised the Furna Feia National Park, Rio Grande do Norte, Brazil, and the expeditions to this area occurred monthly between January 2013 and June 2018. In each expedition the quantification of individuals/species in fruiting, using the method of trails and the collection of fecal samples to describe the frugivorous diet of medium and large vertebrates. The patterns of fructification phenology of the zoocoric species were evaluated by means of circular statistics, and the relationship between seasonality of fruiting and rainfall by simple linear regression tests. Fecal samples were dissociated for the identification of the seeds found in these samples. The phenology of the fruiting of 643 individuals, distributed in 11 zoocoric plant species, was monitored and analyzed. During the rainy season, Sideroxylon obtusifolium, Cereus jamacaru, Ziziphus joazeiro, Commiphora leptophloeos and Bromelia laciniosa exhibited high seasonality of fruiting. At this season, Cynophalla flexuosa also fruited, but presented low seasonality in fruiting. In the dry season Myracrodruon urundeuva, Licania rigida, Cissus sp. and Maytenus rigida showed high seasonality in fruiting. At this station, Phoradendron quadrangulare also fruited, presenting low seasonality in fruiting. Partial asynchrony was observed between the fruiting period of the investigated species, which provided availability of zoocoric fruits throughout all months of the year. However, in the dry season there was a lower number of individuals in fruiting, indicating that this is a critical period for the fruit-dependent fauna in the Caatinga. The intensity of rainfall influenced the fruiting of more than 50% of the zoocoric species, corroborating the prediction of the existence of a relationship between precipitation and fruiting for most Caatinga plants. By means of the analysis of the intact seeds found in the fecal samples, 16 plant species were identified. From these data, a network of interactions between zoocoric fauna and flora was proposed, in which high seed dispersal potential was identified by medium and large vertebrates and high importance of fruits in the diet of these animals. It is suggested that future strategies for the conservation of frugivorous vertebrates of the Caatinga should prioritize the protection of multiple plant species, since the absence of one may imply nutritional risk for animals, especially during the dry season